The Politics of Gender Culture - Paudel, Udaya Raj (Literary Studies, 2020)
Queer: The Problematic of Sexuality and (Sexual) Identity Queer Theory that has turned a derogatory and abusive term homosexuality into a respectable one does not come in a single mode. Though queer theory comes through different forms, the theory developed out of gay and lesbian feminism is more prominent and has become an umbrella term for a coalition of culturally marginal sexual self-identifications. Historically, lesbian feminism split from the mainstream feminism accusing it of representing white, middle class, and heterosexual women and ignoring the existence of black and women with ‘perverse’ sexuality” (Rivikin and Ryan 676). Implicit in its agenda was the assumption of a core lesbian identity that was either biological given or conditioned by psychosocial factors. Lesbian feminism as such then was an attempt of establishing an essential Lesbian identity with an unchanging self (Berten 226). However, a number of lesbian critics, deeply informed by Michael Foucault’s multi-volume History of Sexuality and Derridian critique of coherent self and binary opposition, began rejecting the notion of essential and fixed identity and coherent self and started seeing all forms of sexual identities including lesbian and gay as social constructs and not a biological given.